Melancholic company - Plaza, Nicole Iona G.
Melancholy has been a recurring theme in literature and visual arts among others. It has been a part of the creative process of some artists for as early as the 14th century, such as the literary works of Emily Dickinson and Shakespeare during the Elizabethan era, and in Albert Duhrer's Melancholia I. Through time, how it was perceived and understood evolved; the society, the people, some researchers had continuously changed its definition. Thus, giving melancholy various meanings depending on which particular period it was present. During its earlier discovery, melancholy was simply a black bile, a fluid in the body that is part of the four humors or temperament, it was a scientific and medically inclined term. Feeling melancholic is also considered being clinically depressed. On the other hand, during another period, it was contextualized as something within the boundaries of "romance". But to define it in layman's term, melancholy or melancholia is synonymous to sadness, grief, and mourning. Among all the different definitions of melancholy, my thesis project explores the most layman definition of the word. Melancholy as sadness, and sadness correlated to mourning. Using the images of dead pets as I see as the most related "object" or a representation that could possibly induce the feeling of melancholy, through painting.